Malignant cardiac tumors: a single-centre 25-year review. (14th October 2021) - Garcia Bras, P; Moura Branco, L; Galrinho, A; Castelo, A; Ferreira, V; Mano, T; Reis, J; Grazina, A; Timoteo, A T; Abreu, J; Pinto, E; Coelho, P; et al.
Abstract: Background: Primary cardiac tumors are extremely rare and are usually diagnosed late due to the nonspecific symptoms. Surgery is the main treatment option, and despite chemotherapy, the prognosis remains poor. Cardiac invasion by metastatic tumors, while more common, also entails an unsatisfactory outcome. The aim of this study was to review patients (P) with malignant cardiac tumors that were diagnosed by transthoracic echocardiogram (TTE) or transoesophageal echocardiogram (TOE) in a tertiary center between 1995 and 2020. Methods: Retrospective analysis of clinical data, echocardiographic assessment of tumor location and morphology, histology results and survival outcomes. Results: A total of 44 malignant cardiac tumors were diagnosed: 12 primary tumors (A) and 32 metastatic tumors (B). A: Regarding primary cardiac tumors, the most common types were angiosarcomas (6), undifferentiated pleomorphic sarcomas (2), fibrosarcomas (2), myxofibrosarcoma (1) and primary cardiac lymphoma (1). The mean age of P at time of diagnosis was 43±15 years, 50% male. The most frequent presentation was heart failure symptoms (50%) followed by arrhythmias (20%). 1 P presented with pruritus and polyarthralgias. On TTE, the most prevalent tumor location was in the right-heart chambers (70%) – mostly the right atrium (50%), with mean dimensions of 40±18x27±11 mm. 85% of P had preserved biventricular systolic function and there was severe pericardial effusion in 38%. The most frequent metastatic involvement at diagnosis was pulmonary (33%) and hepatic (33%). 50% of P were submitted to tumor resection and 40% to chemotherapy. Regarding angiosarcomas, the most common immunohistochemical markers were vimentin, CD31 and CD34. The authors found a mortality rate of 10P (83%) in P with primary cardiac tumors, with a median time to mortality of 5.5 (IQR 2–10) months (Figure 1), in a median follow-up of 6.2 (IQR 2.5–15) months (minimum of 20 days and maximum of 19 years). In the latter case, the P was submitted to heart transplantation after diagnosis of a fibrosarcoma and is still alive and well. B: Regarding secondary cardiac invasion, there was a diagnosis of the following primary tumor sites: 12 lung carcinomas, 7 thymomas, 4 lymphomas, 3 hepatocellular carcinomas, 2 bladder carcinomas, 1 parathyroid carcinoma, 1 soft tissue sarcoma, 1 uterine sarcoma and 1 melanoma. The mean age of P was 57±19 years, 57% male. On TTE/TOE the authors found a right-sided chambers predominance (12 P, 38%) vs left-sided chambers in (8 P, 25%), with pericardial metastasis also present in 13 P (41%). Cardiac tamponade occurred in 6P (19%). The mortality rate was 75% (24P), with a median time to mortality of 1.1 (IQR 0.6–3.8) months (minimum of 7 days, maximum of 44 months), in a median follow-up of 2.3 (IQR 0.8–14) months. Conclusion: Cardiac malignant tumors generally present in a late stage with a dismal prognosis. When possible, heart transplantation can be an option with a favourable outcome. Funding Acknowledgement: Type of funding sources: None.